Hannah Arendt: a reconstrução do homem político - Rosa, Doriedson Alves da (2019)
The theme of This research is "Hannah Arendt : the reconstruction of the political man, presented above all, from her political conceptions present all through the diverse work of Hannah Arendt. The central problem of this dissertation is the possibility of reconsidering the political condition of the current man having as his object the analysis Arendt's political thought; and in a collective basis the specific aims are: Presenting the main elements of Arendt's political theory, drawing a profile in which can identify this political being and in the end, determining the ethical character that guides his conduct and political practice. The Importance of this research is in the fact that it proposes, in a certain way, rethinking the political reality from categories as public space, liberty, action and speech, which are, according to Arendt's political theory, show aspects for the political practice; and not only as expected results from theoretically partisan and representative nature, just like it happening the major part of the current political systems. Methodologically this research was based, essentially in the study of Arendt's works, and other critics and commentators, in this sense, in doing that, it was possible to get to the outcome in which the "Arendtician political man " depends, for his public and factual existence, on the acceptance of the responsibility and authorship in a plural world who's permanence without it is not possible. Furthermore, this world, ordinary and public, object of public and Collective life, only begins to exist at the moment that he becomes a public agent, acting in the publicity of common life, while, one more subject who can create the inexistent, and the contingency and its Singularity and unicity, through Its political man's condition.